Marketing Management Crisis and Brand De-identification: A Qualitative Study on the Multinational Product Boycott Movement in Indonesia - Leni Sugiyanti; Ayu Ambarwati; Ratna Sari Dewi; Rendy Permana; yulita (Jurnal Ragam Pengabdian, 2026)
This research explores the phenomenon of consumer boycotts against multinational brands in Indonesia driven by socio-political issues. Using a qualitative descriptive approach with a triangulation technique, this study examines the mechanism of brand image deconstruction and the shift in consumer loyalty. Data were gathered through in-depth interviews, digital observation, and documentation. The results reveal four key findings: first, the deconstruction of brand equity as consumer priorities shift toward "Ethical Equity"; second, the failure of rigid global narratives to meet local empathetic expectations; third, the rise of consumer ethnocentrism providing momentum for local brands; and fourth, the necessity of a "Hyper-localization" strategy involving authentic social action for brand recovery. This study provides a strategic framework for multinational companies to navigate ethical crises in a sensitive market.